Contesting the green transition: Nickel downstreaming, structural inequality, and the paradoxes of green extractivism - Fatimatuzzahro (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Indonesia, home to some of the world’s largest nickel reserves, has emerged as a central hub in the global electric vehicle supply chain under initiatives of nickel downstreaming. This study aims to examine how nickel industrialization intersects with social, ecological, and spatial inequalities, revealing the paradoxes of green economic growth. Methods: Drawing on theories of political ecology framework, it integrates theories of the resource curse, and green extractivism, to understand the uneven realities of Indonesia’s green transition, a mixed-methods approach was employed, integrating statistical data from the Indonesian Central Bureau of Statistics, deforestation records, health indicators, and civil society reports. The analytical process involves visualizing longitudinal datasets (2019–2024) to detect regional inequalities, which are then linked to qualitative reports to identify patterns of structural neglect and environmental injustice. Findings: The findings indicate that nickel-led industrial growth boosts regional GDP while welfare improvements remain stagnant, inequality persists, and access to healthcare and ecological quality are unevenly distributed across nickel-producing provinces. Deforestation, limited infrastructure, and the dominance of foreign investment reinforce patterns of structural neglect and embed Indonesia within global resource dependency networks. Conclusion: The study concludes that current circular economy policies risk serving as technocratic tools that legitimize extractive industrialism rather than foster genuine sustainability. Achieving meaningful circularity requires prioritizing ecological restoration, community participation, and redistributive justice to ensure that the green transition does not reinforce pre-existing inequalities. Novelty/Originality of this article: This research contributes a novel perspective by linking nickel industrialization with environmental justice, green colonialism, and spatial inequality in Indonesia’s low-carbon development agenda.